Real-time flow measurement in Cache Valley irrigation canals - Thompson, Evan, author; Merkley, Gary, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Increased stress on water resources in Cache Valley, Utah has caused a need for improved water management on the irrigation canals throughout the valley. Through a joint project with the Utah Division of Water Rights (UDWR), the Utah Water Research Laboratory (UWRL), various canal companies, and Utah State University (USU), a data acquisition and telemetry system was expanded to include several irrigation canals which take water from the Logan River. With the cooperation of the Logan River Commissioner and several canal companies, new stations were set up to monitor the flow rate on seven irrigation supply canals. Through the use of digital shaft encoders and a radio telemetry system, real-time flow data are now publicly available on the UDWR website. The installation of this system is expected to help improve water regulation throughout the valley. The readily available flow monitoring data has made water managers' jobs easier, as well as providing water users with a more efficient way of monitoring water levels in order to conserve water throughout the irrigation season.
SCADA and related technologies
Not digitized by CSUL Digital Services.
Presented at SCADA and related technologies for irrigation district modernization, II: a USCID water management conference held on June 6-9, 2007 in Denver, Colorado.